Dietary supplements and herbal medicine for COVID-19: A systematic review of randomized control trials. (August 2021) - Feng, Zitong; Yang, Juan; Xu, Mingzhu; Lin, Run; Yang, Huijun; Lai, Liting; Wang, Yixiao; Wahner-Roedler, Dietlind L.; Zhou, Xuan; Shin, Kyung-Min; Salinas, Manisha; Mallory, Molly J.; et al.
Summary: Background: The world is currently struggling with the Coronavirus disease 2019 (COVID-19) pandemic. Dietary supplements (DSs) and herbal medicine provide a potentially convenient and accessible method for its recovery, but direct evidence is limited. Objective: This study aims to investigate the effectiveness of DSs and herbs in patients with COVID-19. Methods: A systematic literature search was conducted in multiple electronic English and Chinese databases. Randomized controlled trials (RCTs) involving DSs or herbal medicine interventions on patients with COVID-19 from November 2019 to February 2021 were included. Data was extracted, summarized and critically examined. Results: Out of 9402 records identified in the initial search, twelve RCTs were included in this review. Risk of bias of these RCTs was deemed high. Most of the trials were of low methodologic quality. Nine studies showed herbal supplements were beneficial to the recovery of COVID-19 patients; zinc sulfate could shorten the duration of loss of smell but not total recovery from COVID-19. No severe adverse events were reported. Conclusion: Herbal supplements may help patients with COVID-19, zinc sulfate is likely to shorten the duration of olfactory dysfunction. DS therapy and herbal medicine appear to be safe and effective adjuvant therapies for patients with COVID-19. These results must be interpreted with caution due to the overall low quality of the included trials. More well-designed RCTs are needed in the future.